Content of Abscisic Acid and Potassium as Drought Stress Indicator on Soybean - Yonny Koentjoro; F. Deru Dewanti; Sukendah (Nusantara Science and Technology Proceedings)
The extreme evapotranspiration on plants and soil surface is a factor that affects plant growth and production. Specifically, water loss in soybean plants affects the ABA content (abscisic acid) and potassium content in the plant. This study aims to evaluate the content of abscisic acid and potassium as indicators of drought stress in soybean plants. This study was designed following the 1-factor experimental rules and using a completely randomized design. The treatment factor is giving of water consisting of A0 = Giving water 100% normal needs, A1 = Giving water 75% normal needs, A2 = giving water 50% normal needs, A3 = giving water 25% normal needs. The results showed that ABA biosynthesis increased in plants experiencing drought stress, the decreasing giving of water, the ABA levels in the leaves increased. The potassium content in plants shows a positive correlation with water supply, the lower the water supply, cause the lower of potassium content. The relationship between abscisic acid content and potassium content in plants indicated that during the occurrence of water deficiency it would trigger an increase in ABA biosynthesis and this condition caused the potassium content in the plant to decrease (R2 = 0.99). Besides, the treatment of giving water had a significant effect on the variables of relative water content in leaves, number of leaves and weight of seeds per plant. The increase in ABA content and decrease in potassium content in plants is an indicator of plants experiencing drought stress.